2020
DOI: 10.1111/fare.12464
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Typology of Emerging Adult Romantic Relationships: Implications for Relationship Education

Abstract: ObjectiveOur objective was to use multiple romantic relationship dimensions to identify a typology of emerging adult romantic relationships.BackgroundEmerging adult romantic relationships vary in terms of their relational dynamics, emotional and physical intimacy, and commitment. Understanding the diversity in emerging adult romantic relationships is crucial for developing effective relationship education for emerging adults as they make decisions about their romantic partnerships.MethodUsing data from 396 rom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 42 publications
(74 reference statements)
5
13
1
Order By: Relevance
“…Understanding constraint commitment is particularly important because research has indicated that relationships that continue without sufficient personal commitment tend to lead to poorer outcomes for both individuals (Beckmeyer & Jamison, 2020) and couples (Stanley et al, 2006). Our study adds support for the notion that constraints are not universally bad (Knopp et al, 2015) but must be understood within the context of the developing relationship to determine their likely consequences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding constraint commitment is particularly important because research has indicated that relationships that continue without sufficient personal commitment tend to lead to poorer outcomes for both individuals (Beckmeyer & Jamison, 2020) and couples (Stanley et al, 2006). Our study adds support for the notion that constraints are not universally bad (Knopp et al, 2015) but must be understood within the context of the developing relationship to determine their likely consequences.…”
Section: Discussionmentioning
confidence: 99%
“…When young adults feel stuck in their romantic relationships, they may also sacrifice personal goals (e.g., educational or occupational opportunities) to maintain the relationship (Kefalas et al, 2011; Shulman & Connolly, 2013). Thus, relationships being sustained by constraint commitment may create a context that undermines, rather than promotes, individual development and well‐being (Beckmeyer & Jamison, 2020). The present study used qualitative data from young adults to explore the circumstances that lead individuals to remain in relationships after their personal desire to stay together has eroded.…”
Section: Theoretical Context Of Constraint Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as part of the identity development processes of adolescents, integrating experiences that provide a safe discussion and navigation where adolescents can explore their understanding of gender roles, the meaning of a romantic relationship, and ideal partner would be developmentally supportive (Simpson et al 2018, Stanley et al 2020. Since emerging adulthood is now characterized by the process of developing commitment in close relationships, it is considered important to include elements such as evaluating and making decisions about healthy and unhealthy relationships, relationship phases and characteristics, problem-solving and selfregulation in relationships (Beckmeyer andJamison 2021, Davila 2021).…”
Section: Discussionmentioning
confidence: 99%